Level of Knowledge and Family Support toward Medication Adherence among Patient with Diabetes Mellitus in Malang, Indonesia - Nur Lailatul Masruroh1*, Alifia Fatehana Pangastuti2 , Nur Melizza1 , Anggraini Dwi Kurnia1 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Patient compliance with long-term therapy for chronic diseases in developing countries is still low. Efforts tocontrol blood sugar levels remain normal with medication adherence depending on family support and patientknowledge of the disease. This study aimed to determine the relationship between the level of knowledgeand family support with medication adherence in patients with diabetes mellitus in Malang, Indonesia. Thestudy design was cross-sectional. The sample of this study was 48 people with diabetes mellitus recordedin Ciptomulyo Health Center. This study uses a simple random sampling technique. The questionnaire usedconsisted of demographic data, knowledge, family support, and medication adherence. The results of thestudy were that there is no relationship between the variable level of knowledge and medication adherencein patients with diabetes mellitus with a significance value of p = 0.561. There was a relationship betweenfamily support and medication adherence in patients with diabetes mellitus with a significance value of p =0,000 and a Correlation Coefficient value of 0.616 which indicates a significant relationship with a strongdegree of relationship strength. There is a relationship between family support and medication adherencein patients with diabetes mellitus at the Ciptmulyo Health Center. The better the family support, the moreobedient the patient is undergoing treatment.